Xenopus cytoplasmic linker-associated protein 1 (XCLASP1) promotes axon elongation and advance of pioneer microtubules - Marx, Astrid; Godinez, William J.; Tsimashchuk, Vasil; Bankhead, Peter; Rohr, Karl; Engel, Ulrike (Molecular biology of the cell, 2013)
Dynamic microtubules (MTs) are required for neuronal guidance, in which axons extend directionally toward their target tissues. We found that depletion of the MT-binding protein Xenopus cytoplasmic linker-associated protein 1 (XCLASP1) or treatment with the MT drug Taxol reduced axon outgrowth in spinal cord neurons. To quantify the dynamic distribution of MTs in axons, we developed an automated algorithm to detect and track MT plus ends that have been fluorescently labeled by end-binding protein 3 (EB3). XCLASP1 depletion reduced MT advance rates in neuronal growth cones, very much like treatment with Taxol, demonstrating a potential link between MT dynamics in the growth cone and axon extension. Automatic tracking of EB3 comets in different compartments revealed that MTs increasingly slowed as they passed from the axon shaft into the growth cone and filopodia. We used speckle microscopy to demonstrate that MTs experience retrograde flow at the leading edge. Microtubule advance in growth cone and filopodia was strongly reduced in XCLASP1-depleted axons as compared with control axons, but actin retrograde flow remained unchanged. Instead, we found that XCLASP1-depleted growth cones lacked lamellipodial actin organization characteristic of protrusion. Lamellipodial architecture depended on XCLASP1 and its capacity to associate with MTs, highlighting the importance of XCLASP1 in actin-microtubule interactions.
Gesehen am 25.07.2017